Theoretical and methodological approaches to the study of interregional interactions in ensuring economic security - L. M. Averina; N. L. Nikulina; I. V. Naumov (Вестник университета)
The adoption of strategies for the spatial development of the Russian Federation, national and economic security has brought the study of inter-regional interactions up to date. In this regard, the authors have reviewed the theoretical and methodological approaches of domestic and foreign scientists to the issues of interregional cooperation in various branches of science and production. Interpretations of the concepts “inter-regional interaction”, “economic security” and “economic security of the region” are analysed. The role of inter-regional cooperation, especially inter-regional investment projects, as critical factors in ensuring regional economic security is emphasised. Groups of potential risks and risk-forming factors for joint inter-regional infrastructure projects are identified. Interregional projects are classified according to their scope and purpose: 1) in the production sphere; 2) projects promoting innovation; 3) projects aiming at infrastructure development. Examples of existing interregional projects in the Ural Federal District are presented. The study uses general scientific methods, in particular, analysis and synthesis. The results of the study can serve as a basis for the further development of new theoretical and methodological approaches to solving the problems of inter-regional cooperation.